A High Performance Liquid Chromatography Method Development and Validation for the Estimation of Canagliflozin in Bulk and Marketed Dosage Form - Gaikwad, Asmita V. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: An efficient and simple high-performance liquid chromatography (HPLC) method has been developed and validated for the determination of canagliflozin in marketed formulations containing canagliflozin. Materials and Methods: The mobile phase used for the chromatographic runs consisted of 5 mMammoniumformate in water: Methanol (25:75, v/v) The separation was achieved on a Symmetry, Waters C 18 (100 mm × 4.6 mm × 3.5 μm) using isocratic mode. Results and Discussion: Drug peaks were well separated and were detected by a UV detector at 290 nm. The method was linear at the concentration range of 1–10 μg/ml for both the formulations. The method has been validated according to the International Conference of Harmonisation guidelines concerning precision, accuracy, and forced degradation. Canagliflozin limit of detection and limit of quantification (LOQ) were 0.0026 ng/ml and 0.008 ng/ml, respectively. Conclusion: The current research epitomizes the report that deals with the development of a stability-indicating HPLC method for the determination of Canagliflozin in two different brands. Canagliflozin is very sensitive so it is unstable in alkaline, oxidative and thermal conditions but stable in UV light or acid conditions.